On the openness of desire: Meaning-construction and dialogical processes in the swing experience - Jesus, Paulo Renato (2010)
European Journal of Sexology and Sexual Health (Abstracts of the 10th Congress of the European Federation of Sexology), 2010, vol. 19, 51-52., Porto, Portugal.